(untitled) (المجلة الدولية للبحوث العلمية, 2024)
This analytical and inductive study follows the phenomenon of the conflict over the sovereignty between Abbasid Caliphate and Seljuk Sultanate in the era between 447 and 590 A.H. I conceived the roots of this conflict, it’s causes and the development of this rivalry, which extended over one hundred forty years. The Seljuk Sultans done their best to deprive Abbasid Caliphs from the sovereignty, as Buyid kings had done with Abbasid Caliphs from 334 till 447 A.H. According to Seljuk’s rule, the Abbasid Caliphate must be only religious authority. Therefore, the caliph has no right to designate governors, military commanders, even his own bodyguards. If the Caliph al-Muqtadi (422-467 A.H.), shown his weak, while he deals with the first Seljuk Sultan Tughril (447 - 455 A.H.). While, this situation, would not continue during the caliphates of Al-Mustarshid (512 - 529 A.H.), al-Muqtafi (530 - 555 A.H.), and al-Nasir (575 - 622 A.H.). During al-Nasir’s caliphate, the Seljuk’s tyranny over the Abbasid Caliphate had terminated by the killing of the last Seljuk Sultan called Tughril Ibn Alp-Arslan in 590 A.H. When the Abbasid Caliphs would resume their authority in 590 AH.. They actually spread their authority only over Iraq and parts of Persia, while the rest of Islamic world would rule by different independent powers.